Public health : local and global perspectives - Liamputtong, Pranee (Cambridge : Cambridge University Press, 2019)
Public Health: Local and Global Perspectives provides students with a comprehensive overview of Australian and international public health issues and contexts. It introduces the discipline of public health and aims to deepen students' understanding of the determinants of health, historical and theoretical perspectives of public health, current health research and evidence-based practice. This fully revised and expanded edition includes new chapters on ethics in public health, planning and evaluation, individual behavioural change, gender-based health inequalities and public health approaches to drug use. Each chapter features a strong pedagogical foundation, including learning objectives, key terms, illustrative case studies, tutorial exercises, further reading and comprehensive summaries that equip students with a deeper understanding of key concepts. Written by an accomplished author team led by Pranee Liamputtong, Public Health remains an essential learning resource.
Title from publisher's bibliographic system (viewed on 28 Jun 2019).
Keywords: elektronické knihy; electronic books; Public health; Public health -- Australia